(untitled) (International Journal of Engineering and Computer Science, 2014)
The need to find a desired image from large database is shared by many professionals. Because of many problems in text-based image retrieval, the new technology was introduced which is known as Content-Based Image Retrieval. Content-Based Image Retrieval is an active research topic since the last decade. Image retrieval based on low level features like color, texture and shape is wide area of research scope. In this paper, all the methods of color, texture and shape features extraction is described. Researchers can combine any of these methods and can get the highest precision and recall by testing different combinations.